Pengaruh Inflasi dan Pertumbuhan Ekonomi terhadap Tingkat Pengangguran dengan Variabel Intervening Indeks Pembangunan Manusia (IPM) di Provinsi Jambi - Rasyida, Sapa Atul; Mailindra, Wiyan; Sumanti, Eva (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the effect of inflation and economic growth on the unemployment rate with the human development index (HDI) as an intervention in Jambi Province. The data used in this research are data on inflation, economic growth, unemployment rates and HDI for the 2014-2023 period obtained from the Central Statistics Agency (BPS), the method used is quantitative descriptive using multiple regression analysis tools. The results of the research show that partially and simultaneously the variables inflation, economic growth and HDI have no significant effect on the unemployment rate variable in Jambi Province for the 2014-2023 period